2005
DOI: 10.1161/01.str.0000189696.70989.a4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Magnetic Resonance Histograms as a Surrogate Marker and Predictor of Disease Progression in CADASIL

Abstract: Background and Purpose-Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebral small vessel disease caused by mutations in the NOTCH3 gene. MRI is sensitive in detecting preclinical involvement and changes over time. However, little is known about correlations between MRI metrics and clinical measures on a longitudinal scale. In this study, we assessed the role of quantitative MRI (T2-lesion volume and diffusion tensor imaging [DTI]-derived metrics) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 23 publications
(37 reference statements)
13
108
2
1
Order By: Relevance
“…79 In a longitudinal study, in 62 CADASIL subjects the changes in mean diffusivity correlated with changes in the Rankin score, national institute of health stroke scale and structured interview for the diagnosis of dementia of the Alzheimer type, multiinfarct dementia and dementias of other aetiology within a 2-year observation period. 28 Diffusion tensor imaging was also used in early detection 80,81 and monitoring of disease progression from mild cognitive impairment to Alzheimer's disease. 82 Sample size calculation based on 2-year follow-up data in CADASIL patients showed that one would need 1,944 subjects per treatment arm to show a treatment effect of 20% with an 80% power when mean diffusivity is used as the trial outcome.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…79 In a longitudinal study, in 62 CADASIL subjects the changes in mean diffusivity correlated with changes in the Rankin score, national institute of health stroke scale and structured interview for the diagnosis of dementia of the Alzheimer type, multiinfarct dementia and dementias of other aetiology within a 2-year observation period. 28 Diffusion tensor imaging was also used in early detection 80,81 and monitoring of disease progression from mild cognitive impairment to Alzheimer's disease. 82 Sample size calculation based on 2-year follow-up data in CADASIL patients showed that one would need 1,944 subjects per treatment arm to show a treatment effect of 20% with an 80% power when mean diffusivity is used as the trial outcome.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%
“…82 Sample size calculation based on 2-year follow-up data in CADASIL patients showed that one would need 1,944 subjects per treatment arm to show a treatment effect of 20% with an 80% power when mean diffusivity is used as the trial outcome. 28 …”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%
“…Many of the other tests mentioned here are measured against the clock, ie, speed-dependent tests 89 . Patients with CADASIL exhibit markedly slow performance in this type of test.…”
Section: Cognitive Decline and Dementiamentioning
confidence: 99%
“…In the future, neurobiological markers of early injury will probably be used in studies trying to influence the onset and progression of clinical changes; this should help reducing the number of patients needed in therapeutic studies. The search for these markers in MR studies involving analysis of the patterns of appearance and progression of atrophy and accumulation of white matter lesions and other typical structural changes is under way, as well as analyses of diffusion histograms and metabolic relations as assessed by spectroscopy 89,[132][133][134][135] . The main marker of disease progression is, unfortunately, increasing age, which can be seen as a non modifiable risk factor.…”
Section: Treatment Of Cadasilmentioning
confidence: 99%
“…Accordingly, MD histogram parameters have been reported to correlate more with clinical scores than WMH visual rating scales and volumetric data in cSVD both cross sectionally and longitudinally. Furthermore they were more sensitive than clinical scales in detecting change over time [101][102][103][104][105][106] . There are data indicating that the much simpler, quicker and widely available (DWI) derived ADC can be used similarly to DTI derived MD to quantify brain damage due to cSVD (findings of Gunda et al to be published) (Figure 3 and 4).…”
Section: Evaluation With Non-conventional Mrimentioning
confidence: 99%